(untitled) (Belas Infiéis, 2016)
Plurivozes Americanas / American Plural Voices / Plurivoces Americanas is a collection of poems and also little pieces of prose in which different ways of perceiving the realities of the American continent are given a voice. All these varied perspectives converge in an academic effort that, on the one hand, reminds us once again about the importance of translation in our everyday more globalized world and, on the other hand, opens a path of communication between the three predominant languages of the Americas. That is precisely why the decisive threefold task of translation undertaken in the project is placed at the very heart of the collection. Translation is actually what makes the book come to existence; it is what makes us understand all the stories and, in a sense, what makes us hear their voices.